Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1161/jaha.116.004185
|View full text |Cite
|
Sign up to set email alerts
|

Nonobstructive Versus Obstructive Coronary Artery Disease in Acute Coronary Syndrome: A Meta‐Analysis

Abstract: BackgroundDifferences in prognosis and baseline clinical presentation have been documented among patient with acute coronary syndrome and coronary artery disease with obstructive (ObCAD) or nonobstructive arteries (NObCAD), but the rates of events largely varied across single studies. We carried out a meta‐analysis to compare the clinical presentation and prognosis of NObCAD versus ObCAD acute coronary syndrome patients, as well as of the subjects with zero versus mild occlusion.Methods and ResultsSearches wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 54 publications
(157 reference statements)
3
72
0
4
Order By: Relevance
“…Literature prognosis data showed that MINOCA is not a benign condition, with an overall estimated mortality around 3.5-4.5% (Pasupathy et al, 2015;Baron et al, 2016;Pizzi et al, 2016;Barr et al, 2018). This unfavorable outcome might be explained, at least in part, by the low rate of b-blockers, angiotensin converting enzyme inhibitors (ACEI), statins, and antiplatelet drugs prescription.…”
Section: Introductionmentioning
confidence: 99%
“…Literature prognosis data showed that MINOCA is not a benign condition, with an overall estimated mortality around 3.5-4.5% (Pasupathy et al, 2015;Baron et al, 2016;Pizzi et al, 2016;Barr et al, 2018). This unfavorable outcome might be explained, at least in part, by the low rate of b-blockers, angiotensin converting enzyme inhibitors (ACEI), statins, and antiplatelet drugs prescription.…”
Section: Introductionmentioning
confidence: 99%
“…Large retrospective studies of patients referred for nonurgent angiography demonstrated a prevalence of non-obstructive CAD of between 20% and 60% of all referrals. Furthermore, while classically non-obstructive CAD had not been thought to be associated with increased risk of mortality or cardiovascular events, more recent evidence suggests that certain subpopulations with non-obstructive CAD are at heightened risk [26,[32][33][34][35]. In our study, CAD was quantitatively defined as a diameter stenosis ≥ 50% in a major epicardial artery.…”
Section: Discussionmentioning
confidence: 88%
“…Samkvaemt rannsóknum eru MINOCAsjúklingar ólíklegri en sjúklingar með marktaekar þrengingar til þess að vera meðhöndlaðir með viðeigandi lyfjameðferð samkvaemt klínískum leiðbeiningum um meðferð á sjúklingum með kransaeðasjúkdóma. 18,19 Nýlega kom út rannsókn frá Svíþjóð sem veitti í fyrsta skipti innsýn inn í árangur af langtíma lyfjameðferð MINOCA-sjúklinga. Þetta var áhorfsrannsókn (observational study) þar sem 9466 sjúklingum var fylgt eftir og var markmiðið að kanna tengsl meðferðar með einstökum lyfjaflokkum við alvarlega hjartatengda atburði (major cardiac adverse event) við eftirfylgni.…”
Section: Umraeðurunclassified